TINJAUAN YURIDIS TERHADAP DISPARITAS PEMIDANAAN PUTUSAN HAKIM DALAM TINDAK PIDANA PEMBUNUHAN BERENCANA PERKARA NOMOR 742/Pid. B/2016/PN Pbr DENGAN PUTUSAN NOMOR 323/Pid.B/2016/ PT Pbr - Juliani, Chaterine; Effendi, Erdianto; Putri, Adi Tiara (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
In the same case, the law has a different regulation. In legal science commonly known as disparity (disparity of sentencing). According to Oemar Seno adji, disparity is justifiable as long as it is done properly. In writing this thesis the author discusses the problem of Criminal Disparities in Criminal Acts of Murder. Is the factor in the disparity in the decision of the judge in case No. 742 / Pid.B / 2016 / PN Pbr with case No. 323 / Pid.B / 2016 / PT Pbr. What is the ideal application of the disparity in a judge's decision? The research method used is a normative jurdical method in relation to substantive justice. The results showed that in deciding a judge's case subject to Article 197 of the Criminal Procedure Code, namely the judge must have his own judgment in determining the severity or severity of the sentence to be handed down to the defendant, through proof of material in court to support the conclusions in the judge's judgment.The results of this study are that in deciding a case, a judge pays attention to matters or methods accordingly and fairly as there is no political interest, personal interests that can harm either party. In this murder case, a defendant with the initial ZG was sentenced to a nine (9) year prison sentence in the Pekanbaru District Court, but the public prosecutor appealed, and in the Pekanbaru High Court after seeing, examining, and examining the case based on facts, evidence and witness testimony of the defendant then sentenced him to a twelve (12) year prison sentence.Keywords: Disparity-Court Decisions-Judge Considerations